WHAT IS A COMPREHENSIVE THEORY OF LAW? (American Journal of Interdisciplinary Research and Development, 2024)
This article reflects on the importance of philosophy to legal theorists. It is also taught that the law is a rational, legitimate regulator of the use of coercion and violence, and that it is a completely unreasonable regulator of the behavior of both individuals and authorities.